2010
DOI: 10.1073/pnas.1004529107
|View full text |Cite
|
Sign up to set email alerts
|

Cryptochrome 2 and phototropin 2 regulate resistance protein-mediated viral defense by negatively regulating an E3 ubiquitin ligase

Abstract: Light harvested by plants is essential for the survival of most life forms. This light perception ability requires the activities of proteins termed photoreceptors. We report a function for photoreceptors in mediating resistance (R) protein-derived plant defense. The bluelight photoreceptors, cryptochrome (CRY) 2 and phototropin (PHOT) 2, are required for the stability of the R protein HRT, and thereby resistance to Turnip Crinkle virus (TCV). Exposure to darkness or blue-light induces degradation of CRY2, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 49 publications
1
106
2
Order By: Relevance
“…3), we conclude that Tm-2 2 is a peripheral PM-associated protein. These findings are consistent with previous reports that several PM-localized R proteins, such as Arabidopsis RPM1 and HRT, are shown to be peripherally associated with the PM (Boyes et al, 1998;Jeong et al, 2010), and RPS2 is an integral membrane protein (Axtell and Staskawicz, 2003).…”
Section: Discussionsupporting
confidence: 82%
“…3), we conclude that Tm-2 2 is a peripheral PM-associated protein. These findings are consistent with previous reports that several PM-localized R proteins, such as Arabidopsis RPM1 and HRT, are shown to be peripherally associated with the PM (Boyes et al, 1998;Jeong et al, 2010), and RPS2 is an integral membrane protein (Axtell and Staskawicz, 2003).…”
Section: Discussionsupporting
confidence: 82%
“…Light and disease resistance also may be linked via cross-talk between photoreceptor signaling and components of the resistance pathway. Light-dependent resistance to Turnip crinkle virus was shown to require cryptochrome 2 and phototropin 2 (Jeong et al, 2010). By contrast, HR development and local resistance to infection by Pst avrRpt2 were found to be dependent on phytochromes A and B (Genoud et al, 2002).…”
Section: Role(s) Of Light In Sar and Other Immune Responsesmentioning
confidence: 96%
“…There is also evidence that cryptochrome1 (cry1) is a positive modulator of Arabidopsis defense against P. syringae pv tomato DC3000 when plants are exposed to continuous light after pathogen infection (Wu and Yang, 2010). However, other studies, carried out under day/night light cycles, failed to detect any effects of mutations in B photoreceptors on Arabidopsis resistance to this bacterial pathogen (Griebel and Zeier, 2008;Jeong et al, 2010). Moreover, cry1 mutants did not show any obvious susceptibility phenotype in bioassays with the necrotrophic fungus B. cinerea (Cerrudo et al, 2012).…”
Section: Par Photosynthesis and Blue Light Receptorsmentioning
confidence: 99%
“…Similarly, the role of blue light (B) and B photoreceptors in the regulation of defense responses is not well established. Jeong et al (2010) reported that cryptochrome 2 and phototropin 2 are specifically required for resistance protein-mediated Arabidopsis defense against Turnip crinkle virus. There is also evidence that cryptochrome1 (cry1) is a positive modulator of Arabidopsis defense against P. syringae pv tomato DC3000 when plants are exposed to continuous light after pathogen infection (Wu and Yang, 2010).…”
Section: Par Photosynthesis and Blue Light Receptorsmentioning
confidence: 99%